PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MASALAH - Wahyu Widia Sari (Jurnal Edukasi dan Penelitian Matematika, 2020)
This-research aims to develop-student’s  worksheets (LKPD) based on problems for 1st grade students of SMA in 1st semester on Nilai Mutlak and Sistem Persamaan Linear Tiga Variabel material. The research model used is Plomp model-that consists of several types, Preliminary,Prototyping and Assessment Phase. On Preliminary, students analysis, curriculum analysis, and concept analysis have been done. Prototyping is the steps to design LKPD that consists of prototype 1 and prototype 2. On prototype 1 self evaluation and expert review have been done-to see the validity of LKPD that have been developed. On prototype 2 there is one-to-one evaluation, by testing the learning tools which have-been validated toward three students. The last-step is assessment-phase that aimed to see the validity and practicality of LKPD. The result-of this research showed-that LKPD based on problems that developed has been valid and practice. Based on the validator evaluation we can get the result is 86,17% that categorized as very valid and the result of three students that has done one-to-one evaluation is 91% which categorized as vary practical.   Keywords __ Worksheet, Project Based Learning